Kandungan Metilparaben Dan Propilparaben Dalam Krim Wajah Yang Beredar Di Wilayah Labuan Kabupaten Pandeglang - Neng Nurul Fitri; Nita Rusdiana; La Ode Akbar Rasydy (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2024)
Methylparaben and propylparaben are compounds that can be used as antibacterials in cosmetics, one of which is in cream preparations. However, if parabens are used excessively, they can cause side effects in the form of increased estrogen, weight gain, irritation, decreased reproductive health, and premature aging. This study aims to identify and determine the levels of methylparaben and propylparaben contained in face creams circulating in the Labuan Region, Pandeglang Regency using the High Performance Liquid Chromatography method. The mobile phase used was methanol: water (4:6), temperature 25oC, flow rate 1.2 mL/min, wavelength 257 nm using an octadecylsilane (C18) column. The results of the four face cream samples used, the samples with the KW 1 and KW 2 codes were not identified as using the preservative methylparaben, the samples with the KW 3 and KW 4 codes contained methylparaben with levels that were still below the maximum limit set by BPOM, namely 0.4% for single preservative use and 0.8% for mixed preservative use. The average percentage of methylparaben content in KW 3 and KW 4 was 0.21% and 0.20%. Meanwhile, the preservative propylparaben was not identified in samples with the codes KW 1, KW 2, KW 3 and KW 4.